Perancangan Sriwijaya Freshwater Aquarium Safari - Fa'izi, M Khairul; Sary, Reny Kartika (Jurnal TekstuReka, 2024)
The Design of Sriwijaya Freshwater Aquarium is a way to introduce freshwater aquatic biota, educate the public, and a destination in Palembang. This design expects to be able to respond to land conditions and produce an optimal design to persuade tourists. Design data were prepared by using observation, interviews, and literature study methods. The space program in this design includes main facilities (destinations), management buildings, supporting facilities and utilities. A special Space Study (SRK) is an analysis form of main facilities, and some utilities need. While the others used related sources for the type of space needed. The location choices is influenced by transportation and proximity to city landmarks and tourist destinations. The building is a concept of Tangible Metaphor with develop wave, zigzag, arch, and vortex elements as the shape of the main and supporting buildings. Through the analysis, the design of Sriwijaya Freshwater Aquarium Safari in Palembang can respond to land conditions by utilizing a strategic location, producing an optimal design by processing the character of the site and building shape. This could be an idea for supporting education about freshwater aquatic biota, and a new destination to persuade tourists to visit Palembang.